2015
DOI: 10.1007/s11255-014-0907-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of hydronephrosis have effects on micropercutaneous nephrolithotomy?

Abstract: The presence of hydronephrosis does not affect success rates and operative time in micro-PNL procedures significantly. Micropercutaneous nephrolithotomy is technically feasible and efficacious both in hydronephrotic and non-hydronephrotic kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Clinical trials have proven the efficacy and safety of the microperc, especially for isolated lower pole and moderate-sized kidney stones. [3][4][5][6] In our study, in addition to an absence of major complications, stone clearance was achieved using two access tracts in all patients: one for standard PNL and one for microperc. We did not need to perform any additional microperc accesses in our series.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Clinical trials have proven the efficacy and safety of the microperc, especially for isolated lower pole and moderate-sized kidney stones. [3][4][5][6] In our study, in addition to an absence of major complications, stone clearance was achieved using two access tracts in all patients: one for standard PNL and one for microperc. We did not need to perform any additional microperc accesses in our series.…”
Section: Discussionmentioning
confidence: 72%
“…[1] Since its introduction in 2011, micro-percutaneous nephrolithotomy (microperc) has been used increasingly for moderate-sized kidney stones. [2][3][4][5][6] The complete clearance of stones from the kidney is important for preventing recurrence and morbidity in both standard PNL, and microperc, procedures. However, achieving a stone-free status in a single session in cases with complex renal calculi is not always possible.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports on its use are for moderate size stones (10-20 mm) and lower calyceal stones that are difficult to handle using extracorporeal shock wave lithotripsy (ESWL) or retrograde intrarenal surgery (RIRS). 4,[6][7][8]10,12,13,15,16,20,23,[38][39][40] Microperc is also performed for pediatric renal stones, 1,7,18,20,40 pelvic ectopic kidney stones, 4,7,8,20,40 kidney stones following partial nephrectomy, 21 kidney stones in severe kyphoscoliosis, 14,26 bladder stones, 6 stones in the isthmus of a horseshoe kidney, 7,21 and awkward lower calyceal anatomy. 7,21 The ideal scenario for microperc is a single calyceal stone, pelvic stone, or multiple stones parallel to the percutaneous renal tract so that lithotripsy can be completed with a single tract and multiple punctures avoi ded.…”
Section: Discussionmentioning
confidence: 99%
“…Karalar et al 8 found that patients with thicker renal parenchyma had higher PNL success rate in their study conducted with 216 patients underwent PNL operation. Karatag et al 9 investigated the effect of hydronephrosis on microPNL results. They have reported the success rate of microPNL as 91.3% and that the presence of hydronephrosis had no effect on the results of PNL.…”
Section: Discussionmentioning
confidence: 99%